Inflammatory bowel disease masquerading as traveller's diarrhoea. Issue 6 (11th June 2019) - Stewart, Adam; Sowden, David; Sloss, Andrew; Broom, Jennifer
Abstract: Diarrhoea that occurs during or after recent travel is predominantly infectious in nature; however, in atypical or prolonged cases a broader range of aetiologies for diarrhoea must be considered, and a careful history and examination may reveal clues to more sinister causes of diarrhoea. We report two cases in which a recent travel history and a positive stool culture or polymerase chain reaction testing for bacterial pathogens delayed the diagnosis of ulcerative colitis. As a result of severe inflammatory bowel disease, colectomy was the final result in both cases. Early consideration of causes other than infection for traveller's diarrhoea may prevent unnecessary morbidity in young patients.